Internal medicine residents’ perspectives and practice about do not resuscitate orders: survey analysis in the western region of Saudi Arabia - Aljohaney, Ahmed (Adv Med Educ Pract, 2015)
BACKGROUND: The purpose of this study was to analyze the perceptions and practices of internal medicine residents in the western region of Saudi Arabia regarding the implementation of do not resuscitate (DNR) orders to improve future training practices among physicians. METHODS: Medical residents involved in training programs in the western region of Saudi Arabia, including Jeddah, Makah, Medinah, and Taif, were invited to participate in a cross-sectional, anonymous, online survey regarding DNR orders. The 16-question survey was distributed to residents in all training programs in the region using surveymonkey.com, and the results were collected and tabulated. RESULTS: Of 364 residents, 157 completed the questionnaire, resulting in a 43% response rate. The study showed that most (66%) internal medicine residents in the western region of Saudi Arabia participate in DNR discussions with patients and family or surrogate decision-makers. In addition, 43% were observed by faculty members, and half of them (51.9%) reported feeling comfortable during these discussions. Furthermore, most residents believed that additional educational programs would enhance their competence in addressing issues related to DNR discussions. CONCLUSION: This study highlights the need for a structured curriculum to teach skills relating to end-of-life issues such as DNR orders to residents in the Saudi Arabian medical system. The majority of residents surveyed believe they would benefit from additional training in DNR discussions. Therefore, an evidence-based curriculum providing instruction for improving discussions regarding DNR orders would improve physician confidence and effectiveness in caring for critically ill patients.